Long term durability and safety aspects of oxidizing honeycomb catalysts integrated in firewood stoves. (October 2017) - Reichert, G.; Schmidl, C.; Haslinger, W.; Stressler, H.; Sturmlechner, R.; Schwabl, M.; Kienzl, N.; Hochenauer, C.
Abstract: Critical heating operating conditions, as emulated in the safety test series, showed that temperatures below 400 °C at the integrated catalysts result in deposited agglomerations on the flow cross-section area of the catalyst's surface and in the risk of increased pressure drops. The deposited material of safety tests consisted predominantly of carbonaceous components with a share of around 120 g kg −1 of OC and 280–450 g kg −1 of EC. The oxidation potential of deposited carbonaceous material by higher temperatures was confirmed by a minor share of EC and OC (<50 g kg −1 ) on the catalyst's surface when a heating cycle with five batches was performed. Concluding a sufficient heating-up of catalyst integrated stoves is necessary to avoid deposition of carbonaceous agglomerations. The long term tests resulted in deposited agglomerations of mineral particles on the catalyst's surface of both types of catalysts. The metallic honeycomb catalyst was more sensitive regarding blocking which was indicated by total blocked cells and a significant increase of pressure drop by 5.3 Pa. Due to the effect of agglomerated particles gaseous emissions increased significantly (CO around 300%, OGC around 45%) whereas PM emissions were reduced by 63%. The regeneration of catalyst performance was almost completely achieved by cleaning the catalyst with water and pressured air. For processing of blocking the open diameter of cells of the honeycomb catalysts play a relevant role. Therefore, in terms of real-life applicability the ceramic honeycomb catalyst seems to be more suitable compared to the metallic honeycomb catalyst. Highlights: Real-life applicability of catalyst integrated solutions without bypass. Operation safety in long term operation and under critical conditions. Effect of long term operation on catalytic CO, OGC and PM conversion rates. Guideline for real-life application of catalyst integrated solutions.